A new record of Diodon hystrix (Actinopterygii: Tetraodontiformes: Diodontidae) in the Mediterranean Sea - F. Ordines; S. Deudero; J. Sinte-Vila; V. Sbragaglia; R. Fricke; E. Azzurro (Acta Ichthyologica et Piscatoria, 2018)
The spot-fin porcupinefish, Diodon hystrix Linnaeus, 1758, was first recorded in the Mediterranean by Torchio (1963), from the Gulf of Taranto, Italy. There have been no subsequent records, from this sea, ever since. In this paper, we report a new record of D. hystrix from the Balearic Islands, western Mediterranean, fifty-five years after the first record. The fish individual was caught during a spearfishing competition. The social networks and the WhatsApp instantaneous messenger proved to be useful tools for the rapid contact with the scientists who are now reporting this record. In view of the fast growth and spreading of other populations of exotic species in the Mediterranean, fostering the communication between recreational fishers and scientists through these types of digital tools could help in monitoring of the natural environment.